Sustainable rural families: a proposal for a community in southeastern Bogotá - Yate Calvo, Luis Enrique
Summary Sustainability in rural households and communities is a major challenge today. The economic and social dynamics that occur in these environments today are accelerating environmental degradation, actions such as inadequate waste management from agricultural and domestic activities, the excessive and extensive use of natural resources such as water and dependence on fossil fuels, such as firewood, contribute significantly to the gradual decrease in the holistic use of rural areas. The objective of this study is to evaluate the level of sustainability of rural households in the Quiba Alta area in the capital district of Bogotá, Colombia. To this end, a qualitative research methodology was adopted, since it is a method that allows the collection and evaluation of non-standardized data, with the aim of understanding a phenomenon in its natural environment. This is how 30 rural households’ representative of the total number of inhabited homes in the locality were evaluated, with a confidence level of 95%. An evaluation framework based on the concept of Sustainable Livelihoods (SLM) was used (Chambers, R., & Conway, G., 1991). This framework is used as it is not intended to represent an accurate view of reality, but to provide a perspective on the livelihoods of the most vulnerable populations. This research develop an integral evaluation model which approached sustainablity from five essential conditions, each one representing a community development critical dimension: self-management, adaptability, environmental culture, coexistence and productivity. Among the main results, it can be mentioned that the level of sustainability of the households was 22.5%, that is, they do not meet the basic sustainability criteria. The sustainability analysis in the sample of households in the selected rural community allowed a better understanding of the practices and use of natural resources in daily life in the countryside. There was a methodic analysis through which integral understanding was obtained on how community members interact with natural resources in their agricultural and domestic daily contexts It was also evident that there is a clear focus in rural communities towards the implementation of sustainable practices and methodologies in their daily lives.